INTERNALIZATION MANAGEMENT OF RELIGION VALUES THROUGH ISLAMIC EXTRACURRICULAR ACTIVITIES FOR THE ESTABLISHMENT OF CHARACTERS OF STUDENTS OF SMAN 1 MALANG - Thoifah, I’anatut (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study aims to investigate the planning, implementation, and evaluation of religious value internalization through an Extracurricular program of Islamic religious division and its relevance to a character building at SMAN 1 Malang. The data collections of this study were observation, interview, and documentation. In analyzing the data, the researcher used qualitative descriptive analysis which means that she described and interpreted the data to figure out the phenomenon in a real condition. The result of this study showed that the member of students in Islamic religious division planned and implemented the programs and activities based on the religious value through materials, methods, and times they arranged. Besides, the internalization management of religious value through this extracurricular program has relevance to a character building. This extracurricular program also facilitates the students to implement their knowledge into a good character based on religious value. In other words, the students can apply their experience they have got in the classroom into the activities in the extracurricular program, to have a good character, in which it also becomes the purpose and the relevance of internalization management of religious value through an extracurricular program and character building.Keywords: Management of Internalization of Religious Values; Extracurricular Section of Islamic Spirituality; Character EducationÂ